Plaques depicting simha (lion) vyala and ashtadal kamal (lotus with eight petals) - Temples of India Project Team (Jio Institute, 2024)
Tablet-like plaques are placed on the adhisthana (facing east). These plaques depict various types of flora and fauna as well as hybrid creatures like kinnara, vyala, and makara. The plaques are tightly arranged, richly detailed, and deeply carved, creating contrasting shadows that make the artwork look three-dimensional in sunlight. The central artwork of the plaque is in the form of a circular medallion surrounded by a foliage motif. For example, the plaque (on the left) has a depiction of simha (lion) vyala, integrated with creeper motifs that fill the rest of the medallion. The plaque, on the right, features the ashtadal kamal (lotus with eight petals). The plaques are separated by squat pillars which have a square base, an octagonal shaft, and a square capital. The pillars are decorated with ardha padma (half lotus) and kalpa lata (creeper) motifs.